The Ecological Impact of Urban Expansion in Oasis Environments: A combined Cartographic and Landscape Analysis - Dechaicha, Assoule; Arab, Walid; Alkama, Djamel (Geoplanning: Journal of Geomatics and Planning, 2025)
Current patterns of urban expansion are mostly considered as impulsive, leading to numerous negative consequences for our biosphere. This disturbing fact has not gone unnoticed in the sprawling oasis cities of the Algerian Sahara, where palm groves are the primary victim. Furthermore, any approach taken to preserve oasis ecosystems requires considering ecological variables. In this perspective, the present study seeks to highlight the spatial growth process of the Laghouat oasis in southern Algeria, during the period 1986 - 2019. The methodology employed is based on the supervised classification of four Landsat satellite images to initiate a cartographic analysis and a landscape quantification of the land use evolution. The analysis is focused on two LUC classes: built-up areas and palm groves. The results of the cartographic analysis highlighted two completely opposite spatiotemporal trends: a significant growth of built-up areas, against a considerable decline in palm groves. The monitoring of the landscape metrics also revealed two different behaviours: growth by densification and elongation of the urban fabric, versus progressive morcellation and fragmentation of the palm groves. These findings pointed to the negative impact of uncontrolled extensions on both the palm groves and the overall oasis ecosystem. This research highlighted the importance of landscape metrics in assessing various forms of spatial urban growth and may support urban planners in choosing the optimal solutions for oasis sustainability.